High excision repair cross-complementation group 1 expression is associated with favorable prognostic factors in breast cancer - Kim, Dong Hyun (Oncol Lett, 2017)
Distortion of DNA can inhibit transcription and replication, resulting in cell death. The nucleotide excision repair (NER) pathway recognizes and repairs DNA adducts. Excision repair cross-complementation group 1 (ERCC1) is a nuclease that serves a vital role in the NER pathway. Few studies have investigated ERCC1 expression in breast cancer. The aim of the present study was to analyze the association between clinicopathological features and ERCC1 expression in breast cancer. ERCC1 expression was studied in 224 invasive ductal carcinomas by immunohistochemical staining. ERCC1 expression was analyzed as an immunoreactive score, and classified into low and high expression groups. The association between immunohistochemical parameters and clinicopathological features was evaluated. High expression of ERCC1 was observed in 33 cases (14.7%) and was statistically associated with lower T stage (P=0.005), lower tumor size (P=0.001), no lymph node metastasis (P=0.044) and no lymphovascular invasion (LVI; P=0.004). Additionally, high ERCC1 expression was associated with a positive estrogen receptor (ER) (P=0.006) and progesterone receptor (PR) (P=0.001) expression status. Non-triple-negative breast carcinoma occurred more frequently in the high expression group (97%) than the low expression group; however, the difference was not statistically significant (P=0.056). Overall and disease-free survival were also not significantly different between the two groups (P=0.989 and P=0.215, respectively). In conclusion, high ERCC1 expression is statistically associated with lower T stage, smaller tumor size, no lymph node metastasis, no LVI, and positive ER and PR expression. This suggests that ERCC1 is associated with favorable prognostic parameters in breast cancer.